Evaluating parental knowledge of pediatric burns first aid in Ireland and the effectiveness of an educational intervention improving knowledge. Issue 3 (May 2022) - Moore, Christina; Clover, James; Gibson, Louise
Highlights: Baseline knowledge of pediatric burns first aid among Irish caregivers was found to be low. An educational video intervention was assessed as a method of raising knowledge. A significant increase in caregiver knowledge was found post intervention. Abstract: Aim: Burns represent a large portion of injuries attending emergency departments each year, with children accounting for the biggest proportion. Appropriate first aid has been shown to help improve the outcome of burns, and decrease the need for surgical intervention. Several studies outside of Ireland demonstrate inadequate parental knowledge of burns first aid, but few evaluated interventions to improve knowledge. Consequently our aim was to assess parental/caregiver knowledge in Ireland, and determine if knowledge levels could be raised following a short educational video intervention. Methods: An educational video based on current European and British best practice guidelines was produced and shown to parents/caregivers waiting in the Pediatric Outpatients Department after a previously validated pre-intervention questionnaire was completed. A post intervention questionnaire was completed following the video. Questionnaires assessed demographics, previous experience and included scenarios to test parental knowledge. Results: 112 parents/caregivers (81.3% female (n = 91), 18.8% male (n = 21)) were questioned. Baseline knowledge was found to be poor overall, however this significantly improved with a simple educational video (pre-score 31.9%, post-test mean score knowledge 92.1%). Pre- and post-test scores showed a statistical significance (x 2 = 71.117, P < 0.001, 95% CI).No other variables analysed were shown to be statistically significant predictors of pre- or post-test scores (all p > 0.05). Conclusion: The study found poor parental knowledge of burns first aid in Ireland and shows the use of an educational video was effective in raising knowledge levels.